Two-stage low power test data compression for digital VLSI circuits. (October 2018) - Thilagavathi, K.; Sivanantham, S.
Abstract: In this paper, we present a hybrid X-filling and two-stage test data compression (TS-TDC) techniques for digital VLSI circuits to reduce the test power and test data volume respectively. The proposed hybrid X-filling combines adjacent filling and modified 4m filling technique to reduce the switching activities of the scan cells. It divides the unspecified bits present in the test cubes by multiples of 4 to increase the correlation between the consecutive test patterns which in turn provides better run length for test data reduction. The filled test cubes are encoded with two stage test data compression in order to reduce test data volume. In the first stage, the completely specified test sets are encoded using Alternative Statistical Run Length (ASRL) coding to enhance the test data compression. The compressed ASRL test set is encoded further using Run Length based Huffman Coding (RLHC) since ASRL codewords contain the maximum run length of oneâ;;s. Experimental results show that the proposed hybrid filling provides the scan-in average and peak-power transition reduction of 88% and 29% respectively against original test sets. The two-stage test data compression scheme achieves a maximum of 86% and an average of 76% compression ratio for ISCAS'89 benchmark circuits.